Franchisee-based brand equity and performance - Felício, J. Augusto (2014)
This study focuses on the perceptions of franchisees and analyzes the influence of brand equity on franchisee performance. The factors that constitute brand equity are also assessed. Factor analysis was used to generate valid and reliable scales based on a sample of 205 Portuguese franchisee firms, and structural equation modeling methodology was then employed in the analysis. The results show franchisee-based brand equity (FBBE) to be a multivariate factor with strong influence on performance. This study contributes significantly to the literature by showing the perspective of franchisees toward franchising. It also has implications on the adequacy of corporate strategy in achieving performance.